Analysis of clinical characteristics of elderly patients with blood culture-positive bacterial liver abscess - Zhang, Hui-Fang; Chen, Jia-Wen; Li, Shan-Shan; Wu, Shi-Wen; Li, Shu; Liu, Chen-Yi; Cai, Chao; Lu, Ming-Qin (Frontiers in Medicine, 2025)
ObjectiveTo analyze the clinical features of elderly patients with blood culture-positive bacterial liver abscess (BLA) and improve diagnostic and treatment strategies.MethodsElderly BLA patients admitted to our hospital from December 2018 to December 2023 were included in the study. Diagnostic tests included routine blood analysis, biochemistry, C-reactive protein (CRP), procalcitonin (PCT), imaging, and cultures of blood or pus. Treatments involved anti-infective therapy, ultrasound-guided abscess drainage, and supportive care.Results(1) Elderly patients with blood culture-positive BLA had higher rates of prolonged hospital stays (≥2 weeks), ICU admission, biliary system diseases, hepatitis B infection, maximum body temperature ≥ 39°C, and qSOFA scores ≥2 compared to controls (p < 0.05)0. (2) Laboratory findings showed higher levels of total bilirubin (≥34.2 μmol/L), ALT (≥50 U/L), serum creatinine (≥80 μmol/L), PCT (≥5 ng/mL), and lower platelet counts (≤100 × 109/L) in the research group (p < 0.05). ESBL-positive cases and liver abscesses ≤5 cm were more common in the research group (p < 0.05). (3) Complications such as pleural effusion, ascites, pulmonary infections, and extrahepatic abscesses were significantly more frequent in the blood culture-positive group (p < 0.05). (4) Microbiological analysis indicated that Klebsiella pneumoniae was the leading pathogen (87.93%), followed by Escherichia coli. For ESBL-positive infections, E. coli was dominant (75.76%), especially in patients with biliary diseases (75.56%). (5) Logistic regression identified prolonged hospital stay, hepatitis B infection, biliary system diseases, temperature ≥ 39°C, PCT ≥5, and abscess size ≤5 cm as independent risk factors for blood culture-positive BLA. (6) The combined diagnostic indicator showed good predictive ability (AUC = 0.840, sensitivity 76.6%, specificity 72.2%).ConclusionElderly patients with biliary diseases, hepatitis B, high PCT levels (≥5 ng/mL), small abscesses (≤5 cm), and fever (≥39°C) are at higher risk for blood culture-positive BLA. Klebsiella pneumoniae remains the predominant pathogen (87.93%), highlighting the need for prompt empirical antibiotic therapy. The combined diagnostic model offers reliable predictive value for this condition. We developed a predictive model aimed at assisting clinicians in identifying high-risk patients prone to bloodstream infections secondary to BLA. This model provides valuable guidance for clinicians in formulating more rational and individualized treatment strategies.